Pengaruh Dana Pihak Ketiga Dan Modal Terhadap Jumlah Pembiayaan Bank Umum Syariah - Muhammad Fauzan (Universitas Islam Negeri Sumatera Utara, 2020)
The background of this research is the growing business activities of Sharia banking, especially the business activities of Bank Umum Syariah (BUS) in Indonesia. The purpose of this study is to test and analyze the influence of third party funds and capital on the amount of financing of Sharia Commercial Bank (BUS) over the last 4 (four) years, starting from January 2015 to December 2018. The study data used there were 48 months of development of third party funds, capital, and the amount of financing of Bank Umum Syariah (BUS) from January 2015 to December 2018. The stages of the method to be used in this study are research flow chart, data collection, library study, problem identification, preprocess, data analysis (data analysis used i.e. multiple linear regression, normality test, classic assumption test (multicolinearity test and autocorrecord test), statistical test (determination coefficient (R2), statistical F test, and statistical t test), data analysis results, final evaluation, and research approach. The result of this study is that third-party fund variables have a significant effect on the variable amount of financing and capital variables have no effect and are not significant to the variable amount of financing. Then third-party fund variables and capital variables simultaneously significantly affect variable amounts of financing